The vulnerability of flood disaster to the students secondary school at Jampea Island - Feri Padli; Ibrahim; Rusdi (Technium Social Sciences Journal, 2023)
Flood is one of the conditions when overflowing water inundated the lower areas. The occurrence of floods always has both positive and negative impacts. If the flood occurs in residential areas, it will have a more negative impact. Therefore, people should have preparedness to prevent the effects of the flood. In 2022, a flood occurred in the Jampea Islands, Selayar Islands regency, and affected 90% of the population. It was caused by the high rainfall intensity that resulted in the higher river discharge and overflowing into settlements. It was unclear how much loss was caused by the flood, but this phenomenon has traumatized the community. This island has been occupied for hundreds of years. However, it has never been a flood that the water inundated 90% of the island’s land. Since the flood is possible to occur when the high rainfall intensity happens. Hence, this research was conducted to find out how is community preparedness in disaster mitigation. The community was focused on students at the secondary school level (SMA and SMK). Students were selected by considering their readiness to be more proactive in disaster mitigation through learning practices and socialization in the family environment. The data were collected through an online questionnaire and observation, then analyzed with a diagram presentation system. The results found that the aspect of students’ knowledge was still classified as low. While the institutional aspect is still relatively moderate. Therefore, the capacity of students still needs to be strengthened to prevent the magnitude of the risk of flooding.